Reactions of Pd and Pt Complexes with Molecular Oxygen. Issue 45 (10th October 2014) - Scheuermann, Margaret L.; Goldberg, Karen I.
Abstract Knowledge of exactly how metal complexes react with molecular oxygen is still limited and this has hampered efforts to develop catalysts for oxidation reactions using O2 as the oxidant and/or oxygen‐atom source. A better understanding of the reactions of different types of metal complexes with O2 will be of great utility in rational catalyst development. Reactions between molecular oxygen and Pd0–II and Pt0–IV complexes are reviewed here.